Incidences and Reporting vs. Under-Reporting Needle Stick Injury and Exposure to Body Fluids among Medical Student’s Clinical Practice - Tengsujaritkul, Maliwan; Mingkhwan, Nattawut; Wannakul, Thanakorn; Ratanakoset, Piyanut; Thurkrathok, Thanawut; Hongchoktawee, Sudarad; Pinitsoontorn, Somdej; Kanato, Manop (Srinagarind Medical Journal, 2013)
Background and objectives: Needle stick injury (NSI) or exposures to patients’ body fluids are the second most common work-related accidents among medical students and yet these are under-reported. This study aims to examine the incidence of NSI or exposure to patients’ body fluids among the 4thyear medical students at Srinagarind hospital. Methods: This study was descriptive study. There were 150 4th year medical students who worked in Srinagarind hospital during March 2012 -February 2013 completed the questionnaire. Data were analyzed using descriptive statistics included frequency, percentage, mean, SD, median, IQR and 95% CI. Results: Response rate was 91.3% (137/150). The combined prevalence of NSI or exposure to body fluids was 52.6% (n=72) [95%CI 45.7, 63.2].The incidence of non-reporters was 65.3% (n=47) because they thought (a) the injury was not serious and the risk of severe infection was low (33.8%) (b) the laboratory result was negative (24.8%) or (c) the process is too cumbersome (24.1%). Over one-third (34.7%; n=25) [95%CI 24.1, 46.9] reported an incident because (a) they were afraid of severe infection (31.9%) (b) did not yet know the laboratory sample (23.6%) and (c) the laboratory result was positive (18.1%). Conclusions: The Incidence more than a half of population studies and two-third is under-reporting. The main reasons for under-reporting were the injury was not considered serious and the risk of infection was considered low. The factor most associated with reporting was fear of severe infection. Keyword: Incidences, Needle stick injury, body substance, medical student